Reconsidering the phyllotaxy significance of seedlings in Clematis - Cheng, Jin; Yan, Shuang-Xi; Liu, Hui-Jie; Lin, Le-Le; Li, Jin-Yu; Liao, Shuai; Li, Liang-Qian; Xie, Lei (Phytotaxa, 2016)
The taxonomic significance of Clematis seedling morphology has been emphasized for decades. However, seedlings of almost 75% of Clematis spp. have not been observed directly. This study germinated achenes and described the seedlings of 14 Clematis taxa, 10 of which have not been reported. The results show that five species and one variety, such as C. acerifolia, C. acerifolia var. elobata, C. urophylla, C. repens, C. brevicaudata, and C. peterae, had typical type I seedlings and that C. integrifolia and C. hexapetala had type II seedlings. Six species showed atypical seedling morphology as defined in previous studies. Our results are the first to describe that species of sect. Naravelia and sect. Fruticella have seedlings with opposite leaves. However, they were different from type II seedlings. Suppressed or elongated hypocotyls are most likely determined by the habitat temperature of the Clematis. Our results suggest that it may be inappropriate to classify Clematis seedlings into two types, and that this classification trait should be used very carefully.